Women and the Sunda Wiwitan Faith: Maintaining Rights in the Legal System - Hazar Kusmayanti; dede kania; Asti Sri Mulyanti (Faculty of Law, Universitas Pekalongan, 2025)
Constitutionally, freedom of religion and belief has been guaranteed in Constitution. The right to embrace religion and belief in God Almighty. However, local believers often experience discrimination against their civil rights, especially the rights of women. This research will examine how the position of women followers of the Sunda Wiwitan belief and all the problems in maintaining their rights. The approach method used in this research is normative juridical through legal principles, legal systematics, and conducted on norms and principles contained in secondary data, which are scattered in primary, secondary, and tertiary legal materials. The Constitutional Court Decision No. 97/2016 has provided new hope for the indigenous faith community, for women, as an integral part of the Sunda Wiwitan community. Women's challenges and difficulties in facing various forms of discrimination to obtain civil rights, such as birth certificates and marriage certificates, are bureaucratic obscurity and lack of understanding of women's rights that often prevent access to public services, which they should receive. In addition, social stigma and negative community views towards traditional beliefs further exacerbate the nuances of this condition. The presence of local women leaders of Sunda Wiwitan, signifies a courageous effort to fight for the rights of indigenous peoples and advocate for more inclusive change. Their efforts show that women in the Sunda Wiwitan community not only play a role as cultural preservationists, but also as agents of change who fight for justice and equality.